2020
DOI: 10.1016/j.diabres.2020.108383
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and COVID-19: What was known and what is really new?

Abstract: Diabetes is one of the most relevant co-morbidity in worsening the prognosis of COVID-19 [1]. Data is also showing that hyperglycemia, in both people with or without diabetes, is an important risk factor for death in COVID-19 [2-5]. A. Sing is reporting some important aspects of this finding [2]. In summary, evidence shows: Conflict of Interest: AC does not have conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 18 publications
3
59
0
2
Order By: Relevance
“…It is crucial to highlight that besides preventing contagion, measures should focus on minimizing the risk of aggravation in case of infection. Different research groups reported that blood glucose levels (BG) were independently associated with odds of hospitalization, severity, and death in COVID-19 [6,17,21,22,23,24]. In addition to HbA1c levels [17,21], higher and more variable BG increased ICU admission and death rate [6,22,23].…”
Section: Impact Of Covid-19 On People With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to highlight that besides preventing contagion, measures should focus on minimizing the risk of aggravation in case of infection. Different research groups reported that blood glucose levels (BG) were independently associated with odds of hospitalization, severity, and death in COVID-19 [6,17,21,22,23,24]. In addition to HbA1c levels [17,21], higher and more variable BG increased ICU admission and death rate [6,22,23].…”
Section: Impact Of Covid-19 On People With Diabetesmentioning
confidence: 99%
“…Bode et al emphasized that a high proportion of individuals with diabetes and hyperglycemia who were hospitalized (451 out of 1122 patients in 88 US hospitals) presented longer hospital stays respect those who had not glycemic disturbances (5.7 vs 4.3 days), and a higher mortality rate (28.8% vs 6.2%) [23]. Lamentably, these were not unexpected outcomes [24]. Researchers from China had already revealed in 2006 that a history of diabetes and raised plasma glucose levels were independent predictors of morbidity and mortality among patients with SARS [27].…”
Section: Impact Of Covid-19 On People With Diabetesmentioning
confidence: 99%
“…[4,5] Nevertheless, robust risk quantification of poor COVID-19 outcomes across wide array of admission BG levels has yet to be well-established. Furthermore, some studies have argued that the prognostic value of admission BG level is primarily driven by diabetes [6,7], while some others stated that the effect may be independent of diabetes history [8,9], thus emphasizing the need to establish a firm evidence on the current premises. Therefore, this review intends to summarize the current knowledge regarding the role of admission BG level in determining the prognosis of COVID-19 patients, thus contributing to risk stratification and patient management in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that diabetes is one the most relevant co-morbidities in affecting the prognosis of the COVID-19 [1]. However, it is not simply the presence of diabetes but the level of hyperglycemia during the disease that impacts on the prognosis [6]. This is true also for people without diabetes but with hyperglycemia during COVID-19 infection [6].…”
Section: Diabetes and Hyperglycemiamentioning
confidence: 99%
“…However, it is not simply the presence of diabetes but the level of hyperglycemia during the disease that impacts on the prognosis [6]. This is true also for people without diabetes but with hyperglycemia during COVID-19 infection [6]. It is amazing that, excluding some recommendations published by experts in diabetes [7][8][9], in the available National and International professional guidelines and expert recommendations -31 in PubMed accessed and examined on September 18th 2020 -the problem of diabetes and particularly of the need for a strict control of hyperglycemia is completely neglected.…”
Section: Diabetes and Hyperglycemiamentioning
confidence: 99%